How to prepare for company change (Brussels, 2018)
"This booklet is the third in a series of practical and easy-to-read manuals for European workers’ representatives. This time the focus is on facing restructuring, which is one of the most prevalent approaches adopted by companies in response to continuous change in the business environment. The purpose of this manual is to provide EWC and SE WC representatives and members of Select Committees with background information and practical tools and checklists for dealing with various forms of restructuring. As usual, it contains lots of concrete tips and good practice examples and is available in 8 different languages."